Quality model for context sensitive mobile applications (Publicaciones en Ciencias y Tecnología, 2008)
Context-aware mobile applications show special features that can affect the software development process. These systems must run on heterogeneous computing platforms, must adjust to the capacities of different access devices and adapt to different contexts of use. The quality of service to the user is guaranteed by the way the environment is responding, which is facilitated by the context of use. This aspect is crucial in mobile applications, often wireless, demanding the quality of these services. The service level is specified by a quality model. The goal of this work is to define the quality model for the context-aware mobile applications domain. The importance of this model is the specification of the quality requirements for the final software product and it can be used for a quantitative evaluation of all the software products obtained during the development process. A taxonomy called RECLAMO (Requirements Classification Model) and the new standard ISO/IEC 25030 are used to define the quality model.
Keywords: context-aware applications; quality model; RECLAMO; ISO/IEC 25010; ISO/IEC 25030